Plotinus' seminar on the Symposium - Sabo, Theodore (Journal for late antique religion and culture, 2017)
The evidence of the Vita Plotini is that Plotinus held a seminar on Plato's dialogue the Symposium in Rome in the third century. Although he was not himself a speaker at the seminar he owed much to the dialogue in his Enneads, most notably to the speech of Diotima. Ennead 3.5 is his exegesis of Diotima's myth of the union of Poverty and the drunken Plenty, and it displays his typical inconsistency and brilliance. Elsewhere in the Enneads he treats Diotima's final mysteries, largely agreeing with her except for his insistence that the final vision is not of the Form Beauty but of the dwellingplace of the Forms that is the Nous.